THE ADVANTAGES OF LEARNING ENGLISH THROUGH ENGLISH LITERATURE. - Xabibullayeva Gulsanam (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Learning a language is not just about mastering grammar rules and expanding vocabulary; it is also about understanding the culture, emotions, and history behind the words. One of the most enriching ways to learn English is through its literature. English literature offers a window into the soul of the language, allowing learners to immerse themselves in its beauty, depth, and diversity. Here are some key advantages of learning English through literature: Firstly, English literature introduces learners to a vast array of words, phrases, and expressions that are often absent from textbooks. Classic works like Shakespeare’s plays or modern novels by authors such as Jane Austen and Charles Dickens are filled with poetic language and idiomatic expressions. For example, reading "To be, or not to be: that is the question" from Shakespeare’s Hamlet not only teaches grammar but also helps learners appreciate the philosophical depth of the language.